Fibrin biopolymer sealant and aquatic exercise association for calcaneal tendon repair - Hidd, Silvia Maria Cardoso Magalhaes; Tim, Carla Roberta; Dutra Jr, Eneas de Freitas; Martins Maia Filho, Antonio Luiz; Assis, Livia; Ferreira Jr, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; Silva, Jose Figueiredo; Amaral, Marcello Magri (Acta Cirurgica Brasileira, 2021)
Purpose: The aim of this work was to analyze the effect of fibrin biopolymer sealant (FS) associated or not to aquatic exercise (AE) on the calcaneal tendon repair. Methods: Forty-four female Wistar rats were randomly divided into four experimental groups: Lesion control (L), Lesion and FS (LS), Lesion and AE (LE) and Lesion and FS associated to AE (LSE). The edema volume (EV), collagen ratio, and histopathological analysis were evaluated after 7, 14, and 21 days of partial tendon transection. Results: The EV was statistically reduced for all treatment groups after 7 and 21 days when compared to L group. The LS and LSE had the highest EV reduction after 21 days of treatment. The FS group didn't induce tissue necrosis or infections on the histopathological analysis. It was observed tenocytes proliferation, granulation tissue and collagen formation in the tendon partial transection area in the FS group. The LSE demonstrated higher amount of granulation tissue and increased the collagen deposition at the injury site. Conclusions: Our data suggests that the therapeutic potential of the association of heterologous fibrin biopolymer sealant with aquatic exercise program should be further explored as it may stimulate the regeneration phase and optimize calcaneal tendon recovery.
Keywords: Biopolymers; Tendons; Achilles Tendon; Rats